Anisotropic Finite Element Modeling Based on a Harmonic Field for Patient-Specific Sclera. (7th February 2017) - Jia, Xu; Liao, Shenghui; Duan, Xuanchu; Zheng, Wanqiu; Zou, Beiji
Abstract : Purpose . This study examined the influence of anisotropic material for human sclera. Method . First, the individual geometry of patient-specific sclera was reproduced from a laser scan. Then, high quality finite element modeling of individual sclera was performed using a convenient automatic hexahedral mesh generator based on harmonic field and integrated with anisotropic material assignment function. Finally, comparison experiments were designed to investigate the effects of anisotropy on finite element modeling of sclera biomechanics. Results . The experimental results show that the presented approach can generate high quality anisotropic hexahedral mesh for patient-specific sclera. Conclusion . The anisotropy shows significant differences for stresses and strain distribution and careful consideration should be given to its use in biomechanical FE studies.